PENGARUH PULSED LIP BREATHING EXERCISE TERHADAP PENURUNAN SESAK NAPAS PADA PASIEN PENYAKIT PARU OBSTRUKTIF KRONIK (PPOK) DI RSU ROYAL PRIMA MEDAN 2018 - Silalahi, Kristina L (Jurnal Keperawatan Priority, 2019)
Chronic Obstructive Pulmonary Disease (COPD) is a lung disease characterized by a limited flow of air in the respiratory tract that is not completely reversible. Exercise Pursed Lip breathing exercise can reduce respiratory muscle spasm, clear the airway, relieve respiratory tract. This type of research is quasi experimental with one-group design pre-post test design. The research population consists of 8 people with sampling using 8 saturated sampling techniques. The results of the research before pulsed lip breathing exercise that respiratory rate of respiratory sufferers as many as 7 people (88.9%), shortness of breath weight 1 person (11, 1%), and who experienced mild breathlessness did not exist. After Pulsed Lip Breathing Exercise, 6 breathless breath less (77, 8%), moderate shortness of breath 2 people (22, 2%), and those with severe shortness of breath did not exist. The Wilcoxon test results at the time of the pre-test the mean value was 2.13 and the median value was 2.00. At the time of the post test the mean value was 1.25 and the median value was 1.00. The value of Z was -2.646 with p value of 0.008 <0.05. it means that Ha is accepted which means that there is an effect of pulsed lip breathing exercise on the decrease in shortness of breath in patients with chronic obstructive pulmonary disease (COPD) at Royal Prima Hospital Medan in 2018. It is expected that respondents will be able to improve their pulsed lip breathing exercise regularly to get a better decrease in shortness of breath than before.